Hubungan Antara Komitmen Organisasi Dengan Persepsi Terhadap Disiplin Kerja Pada Pegawai Negeri Sipil - Broto Nugroho, Ismarsono, Achmad Dwityanto, S.Psi, M.Si (2017)
ABSTRACT In the process of the development of the governance fields, especially in increasing the social services, it obtained more and more criticism. Therefore, the services for people are demanded to increase the quality of all government administration orders including the increase in the ability and the discipline in the implementation. The purposes of this research are: 1) to know the correlation between the organization commitment and the perception on the work discipline in the Civil Servants. 2) to know the levels of the organization commitment and perception on the work discipline. 3) to know the effective contribution of the organization commitment on the perception on the work discipline. Hypothesis proposed is that there is a positive correlation between the organization commitment and the perception on the work discipline in Civil Servants. This research did not do sampling. It is because this research used a population study because not all civil servants were involved to be the subjects of the research, they are 80 people. Based on the results of the data analysis, it is known that there is a positively significant correlation between the organization commitment and the work discipline. The positive correlation from this research describes that the higher the organization commitment, the higher the perception on the work discipline of the civil servants will be, and vice versa. It can be revealed by the score of the correlation coefficient as much as 0.266 with the sig is as much as 0.008; p < 0.05 and the level of the organization commitment in DPPKAD of Boyolali Regency is included in a moderate category. The empirical means for the organization commitment is 102.35, meanwhile, the hypothetical means of the scale of the organization commitment is 104. The level of the work discipline in DPPKAD of Boyolali Regency is included in a high category. The empirical means for the work discipline is 141.07, meanwhile, the hypothetical means of the work discipline is 135. The effective contribution of the organization commitment on the work discipline is as much as 7.1% then there is 92.9% of the rest which is influenced by variables which can influence the work discipline except the variable of the organization commitment. Keywords: organization commitment, perception and work discipline